Aesthetic and Emotional Effects of Meter and Rhyme in Poetry - Obermeier, Christian; Menninghaus, Winfried; von Koppenfels, Martin; Raettig, Tim; Schmidt-Kassow, Maren; Otterbein, Sascha; Kotz, Sonja A. (Frontiers in Psychology, 2013)
Metrical patterning and rhyme are frequently employed in poetry but also in infant-directed speech, play, rites, and festive events. Drawing on four line-stanzas from 19th and 20th German poetry that feature end rhyme and regular meter, the present study tested the hypothesis that meter and rhyme have an impact on aesthetic liking, emotional involvement, and affective valence attributions. Hypotheses that postulate such effects have been advocated ever since ancient rhetoric and poetics, yet they have barely been empirically tested. More recently, in the field of cognitive poetics, these traditional assumptions have been readopted in a general cognitive framework. In the present experiment, we tested the influence of meter and rhyme as well as their interaction with lexicality in the aesthetic and emotional perception of poetry. Participants listened to stanzas that were systematically modified with regard to meter and rhyme and rated them. Both rhyme and regular meter led to enhanced aesthetic appreciation, higher intensity in processing, and more positively perceived and felt emotions, with latter finding being mediated by lexicality. Together these findings clearly show that both features significantly contribute to the aesthetic and emotional perception of poetry and thus confirm assumptions about their impact put forward by cognitive poetics. The present results are explained within the theoretical framework of cognitive fluency, which links structural features of poetry with aesthetic and emotional appraisal.